Study of mindfulness effectiveness among neurotic students based on EEG - Nik Amalia Nadirah, Nik Rashidi; Lila Iznita, Izhar; Sebastian, Patrick; Zaid, Omar; Mohd Fakhizan, Romlie; Hamzah, Sakidin; Dafrizal, Samsudin; Abdul Rahman, Mohd Kasim; Adytia, Didit (Institute of Electrical and Electronics Engineers Inc., 2023)
Anxiety and stress are commonly reported problems related to working life where physical and mental conditions become worse due to environment exhaustion. An objective assessment is conducted to analyze brain signals using electroencephalography (EEG). In this study, Cognitive Ability Modulation Index (CAMI) was measured by calculating the relative band power in the prefrontal lobe to measure cognitive ability. It is observed that CAMI showed higher value in post-MI than pre-MI, especially for the Fp1 channel which relates to the outcome of a positive impact of MI in reducing anxiety and stress while performing the Stroop Colour Task. To validate CAMI as a suitable measure for effectiveness of Mindfulness Intervention (MI) towards reducing anxiety and stress among neurotics, classification of CAMI before and after MI is performed. The classification achieved 80% accuracy using the Quadratic Support Vector Machine classifier.